Analisis Dampak Kurikulum Merdeka Terhadap Pengajaran Dan Pembelajaran Di Sekolah Dasar - Saudah Khodijah; Aprilia Kinantika Sari; Aulia Mayasari; Nella Rofisian (Jurnal Pendidikan Sosial Dan Konseling, 2024)
Education is a learning process that always develops with the times. The Independent Curriculum, which was introduced as an effort to improve the quality of education, gives principals the freedom to design learning that suits students' needs. The method used in this study is a qualitative approach with data collection through interviews. The results of the study indicate that the implementation of the Independent Curriculum has a positive impact. However, challenges in educator training, policies and provision of resources are obstacles in the implementation of this curriculum. The learning process is an activity that is processed through the stages of design, implementation and evaluation. Thus, ongoing support is needed from the government and educational institutions to optimize the implementation of the Independent Curriculum so that it can effectively improve the quality of basic education in Indonesia